Cardiac Rehabilitation Based on the Walking Test and Telerehabilitation Improved Cardiorespiratory Fitness in People Diagnosed with Coronary Heart Disease during the COVID-19 Pandemic - Batalik, Ladislav (Int J Environ Res Public Health, 2021)
This study investigated an alternative home-based cardiac telerehabilitation model in consideration of the recommendations for the COVID-19 quarantine of people diagnosed with coronary heart disease (CHD). We hypothesized that using a 200 m fast walking test (200 mFWT) and telerehabilitation would create an effective alternative cardiac rehabilitation (CR) intervention that could improve cardiorespiratory fitness. Participants (n = 19, mean age 60.4 ± 9.6) of the 8-week intervention performed regular physical exercise at the target heart rate zone determined by calculations based on the 200 mFWT results. In our study, the participants were supervised using telerehabilitation. A total of 84% of participants completed the 8-week intervention. No adverse events were reported during telerehabilitation. The study participants noted a significant improvement (p < 0.001) in cardiorespiratory fitness expressed by an 8% reduction in the walking test time (Δ 8.8 ± 5.9 s). Home-based telerehabilitation based on 200 mFWT effectively increased the cardiorespiratory fitness in people with CHD with a low to moderate cardiovascular risk. This was a novel approach in CR during the COVID-19 pandemic. As research in this area is justified, this paper may serve as an alternative method of providing healthcare during the COVID-19 pandemic and as a basis for further upcoming randomized controlled trials.